The LIFE Cognition Study: design and baseline characteristics - Sink, Kaycee M (Dove Medical Press, 2014)
Observational studies have shown beneficial relationships between exercise and cognitive function. Some clinical trials have also demonstrated improvements in cognitive function in response to moderate–high intensity aerobic exercise; however, these have been limited by relatively small sample sizes and short durations. The Lifestyle Interventions and Independence for Elders (LIFE) Study is the largest and longest randomized controlled clinical trial of physical activity with cognitive outcomes, in older sedentary adults at increased risk for incident mobility disability. One LIFE Study objective is to evaluate the effects of a structured physical activity program on changes in cognitive function and incident all-cause mild cognitive impairment or dementia. Here, we present the design and baseline cognitive data. At baseline, participants completed the modified Mini Mental Status Examination, Hopkins Verbal Learning Test, Digit Symbol Coding, Modified Rey–Osterrieth Complex Figure, and a computerized battery, selected to be sensitive to changes in speed of processing and executive functioning. During follow up, participants completed the same battery, along with the Category Fluency for Animals, Boston Naming, and Trail Making tests. The description of the mild cognitive impairment/dementia adjudication process is presented here. Participants with worse baseline Short Physical Performance Battery scores (prespecified at ≤7) had significantly lower median cognitive test scores compared with those having scores of 8 or 9 with modified Mini Mental Status Examination score of 91 versus (vs) 93, Hopkins Verbal Learning Test delayed recall score of 7.4 vs 7.9, and Digit Symbol Coding score of 45 vs 48, respectively (all P<0.001). The LIFE Study will contribute important information on the effects of a structured physical activity program on cognitive outcomes in sedentary older adults at particular risk for mobility impairment. In addition to its importance in the area of prevention of cognitive decline, the LIFE Study will also likely serve as a model for exercise and other behavioral intervention trials in older adults.